The Effect of Communication and Self Efficacy on Employee Performance through Job Satisfaction as an Intervening Variable Study at the Pratama Pati Tax Service Office - Adhi Winarto; Mamik Indaryani; Mochamad Edris (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the effect of communication and self-efficacy on employee performance through job satisfaction as an intervening variable. The research data uses primary data in the form of a questionnaire. The method of determining the sample used purposive sampling and obtained a sample of 120 KPP Pratama Pati employees. The data analysis used in this study is the Structural Equation Model. Based on the results of data analysis, it can be concluded that communication and self-efficacy have a significant effect on job satisfaction. The results of this study also state that communication, self-efficacy and job satisfaction have a significant effect on employee performance. Job satisfaction is able to mediate the effect of communication and self-efficacy on employee performance.